Risk Factors of Anomalous Cord Insertion Among Singleton Births at the University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia: An Institution-Based Cross-Sectional Study - Aragie H; Asmare Y; Tenaw B (Dove Medical Press, 2021)
Hailu Aragie, Yared Asmare, Bahiru Tenaw Department of Human Anatomy, School of Medicine, College of Medicine and Health Science, University of Gondar, Gondar, EthiopiaCorrespondence: Hailu AragieDepartment of Human Anatomy, School of Medicine, College of Medicine and Health Science, University of Gondar, PO. Box 196, Gondar, EthiopiaEmail hailuaragie995@gmail.comIntroduction: Anomalous cord insertion causes bad pregnancy outcomes. Therefore, knowledge on the prevalence and risk factors of anomalous cord insertion will reinforce the prenatal care by health providers in addressing the adverse outcome caused by this abnormality.Methods and Materials: An institution-based cross-sectional study design was conducted among 421 singleton births at the University of Gondar comprehensive specialized hospital. A systematic random sampling technique was used to select study participants. Data were collected by using a structured questionnaire and checklist and was entered into epi-data version 3.1 and then exported to SPSS version 20 for data cleansing and analysis. Bi-variable and multivariable logistic regression was employed to identify factors associated with anomalous cord insertions. Crude and adjusted odds ratio with a 95% confidence interval was calculated to identify the independent risk factors for anomalous cord insertions.Results: The prevalence of anomalous cord insertion was 9.0% in singleton pregnancies. Independent risk factors for ACI were advanced maternal age (AOR= 4.77), primiparity (AOR=3.87), maternal chronic hypertension (AOR=3.23), previous caesarian delivery (AOR=3.28), and use of IUCD before pregnancy (AOR=3.91).Conclusion: Anomalous cord insertion was reported in approximately one-tenth of singleton deliveries in the representative Ethiopian population. Advanced age, primiparity, hypertensive disorder, history of caesarian section, and IUCD usage before pregnancy were associated with increased risk of anomalous cord insertion.Keywords: prevalence, anomalous cord insertion, singleton births, Gondar, Ethiopia